1987
DOI: 10.1136/thx.42.4.278
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of bronchograms and chest radiographs in patients with chronic sputum production.

Abstract: Bronchograms and plain chest radiographs of 27 patients with chronic sputum production were reported separately in random order and independently by two pulmonary radiologists to establish the diagnostic rate of each investigation and to assess interobserver variation.Both Two main groups of patients with bronchiectasis were identified by bronchography: 11 with bronchiectasis alone and eight with bronchiectasis and bronchographic features suggestive of "chronic bronchitis". There was no clinical difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…Although historically the serial evaluation of chest radiographs has been reported as being suitable to document progression of CF [42] and non-CF bronchiectasis [43], it has been well established that HRCT of the chest provides more detailed information [44][45][46]. Utilising HRCT scans and a validated CT score in this study is a major strength in comparison with other work that uses chest radiograph assessment to compare with exercise.…”
Section: Discussionmentioning
confidence: 96%
“…Although historically the serial evaluation of chest radiographs has been reported as being suitable to document progression of CF [42] and non-CF bronchiectasis [43], it has been well established that HRCT of the chest provides more detailed information [44][45][46]. Utilising HRCT scans and a validated CT score in this study is a major strength in comparison with other work that uses chest radiograph assessment to compare with exercise.…”
Section: Discussionmentioning
confidence: 96%
“…1,5,7 In infants and pre-school children with bronchiectasis, it is mostly challenging to obtain high quality sputum. Moreover, chest radiography 9 and spirometric tests are not sensitive enough to predict the exacerbations. 8,10 In the present study, MPV values are found significantly lower during acute exacerbation periods of bronchiectasis when compared to non-exacerbation periods and the values of healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 Besides, chest radiography and spirometric analysis are not sensitive enough in monitoring disease progression and predicting exacerbations. 8,9,10 Novel and appropriate parameters are needed to predict exacerbations and follow disease activity in children. It is known that platelets play a role in either pathogenesis of chronic inflammation during the development of bronchiectasis or progression and exacerbation of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Currie et al (1987) in a study of 27 patients with chronic sputum production evaluated bronchographically showed that there was a significant interobserver variability when studies were interpreted by two well-trained bronchographers. Agreement was reached only in 19 out of 27 (70%) by one radiologist only.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that bronchography may be more limited in its utility than previously thought. 1 We did a random study in 50 patients in our hospital who were clinically suspected to have bronchiectasis. HRCT's were performed on these patients on Toshiba sub-second Spiral CT Scan.…”
Section: Discussionmentioning
confidence: 99%